The Responsibility of Crane Company in terms of The Loss Occurred during The Sea’s Transport Activity Based on Indonesia’s Civil Law - Ardo Alkautsar; Sinar Aju Wulandari; Zahry Vandawati Chumaida (Transpublika Publisher, 2025)
Transportation activities, whether by land, air or sea, involve parties involved in the transportation process. The parties in the transportation activity have different legal obligations. Different legal obligations can be viewed from the different legal relationships that arise between the parties in transportation and the roles of the parties in transportation. In sea transportation, there are many parties involved with each other and it is even possible to have a legal relationship with parties who are not directly involved in the sea transportation, such as a crane company that is present only to rent crane equipment to the loading and unloading company so that loading and unloading activities can be carried out, which also does not rule out the possibility that the loading and unloading company can create a legal relationship with other parties in the transportation process. In transportation, the parties can also use insurance for both the activities or interests of the transportation process with the aim of reducing the risk of loss that can arise in transportation activities or other events during transportation activities. Within this study, the legal and operational responsibilities of crane companies functioning as intermediary service providers in maritime transportation are being investigated. Using normative legal research methodology with statute and conceptual approaches, the research analyzes Indonesian laws, regulations, and legal materials related to crane company responsibilities in maritime operations. The findings reveal that crane companies bear liability for operational losses, must provide suitable equipment, and should utilize insurance protection for risk transfer.